Guidelines for contributors (2013)
This journal is led by the PROFILE research group of the Departamento de Lenguas Extranjeras, Universidad Nacional de Colombia, Bogotá campus. It is a publication for teachers of English interested in increasing their professional expertise. Starting from the assumption that our professional knowledge is enriched by different members of our academic community, the journal is mainly concerned with sharing the results of classroom research projects undertaken by primary and secondary school teachers as well as teachers of adults. It also includes articles written by teacher educators and guest teachers willing to disseminate reflections and innovations. Furthermore, it shares papers sent by professors of diverse educational levels from different parts of the world and who have also been engaged in carrying out research and innovations in wide-ranging contexts as well as inquiries done by novice teacher-researchers.